Lunar radio Cherenkov observations of UHE neutrinos - Ekers, Ronald; James, C.; Protheroe, R.; McFadden, R. (Elsevier, 2009)
The lunar radio Cherenkov technique uses the moon as a large-volume detector for ultra-high energy (UHE) cosmic rays and neutrinos. We review the issues and techniques needed for sensitive radio detection of nanosecond pulses from UHE neutrino events in the lunar regolith. Historical experiments and limits are discussed. We compare experiments using single telescopes with focal plane array and both incoherent and coherent detection with aperture plane arrays of telescopes. Opportunities for future experiments at both high and low frequencies with massive arrays such as the SKA will be considered. © 2009.